CO-WORKING SPACE SEBAGAI SOLUSI KEBUTUHAN RUANG KERJA BERDASARKAN KARAKTERISTIK STARTUP KREATIF - Refyanti Dwi Pramedesty; Djoko Murdowo; Irwan Sudarisman; Andreas D. Handoyo (Ide dan Dialog Desain Indonesia (Idealog), 2018)
Creative startup are currently growing rapidly in Indonesia, as well as in the city of Bandung. The main user characteristics of the creative startup have a unique and space preference that can develop fresh and new ideas. The characteristics of the user will affect the design especially on the character of the design. This paper will analyze the relevance of interior design that can accommodate users with creative startup characteristics and how to present interior design that can stimulate and create creative ideas for users. The research method is qualitative research, by doing field observation and questionnaire dissemination. This paper uses a sample of co-working space users in Bandung, as well as creative startup that stand in 5 dominant sector in Bandung. The results showed the required space of co-working space with preference on interior element.